Sensors and biosensors based on magnetic nanoparticles - Rocha-Santos, Teresa A. P.
Magnetic nanoparticles (MNPs) have attracted a growing interest in the development and fabrication of sensors and biosensors for several applications. MNPs can be integrated into the transducer materials and/or be dispersed in the sample followed by their attraction by an external magnetic field onto the active detection surface of the (bio)sensor. This review describes and discusses the recent applications of MNPs in sensors and biosensors, taking into consideration their analytical figures of merit. This work also addresses the future trends and perspectives of sensors and biosensors based on MNPs.